2019
DOI: 10.1113/jp278752
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide riboside does not alter mitochondrial respiration, content or morphology in skeletal muscle from obese and insulin‐resistant men

Abstract: Key points This is the first long‐term human clinical trial to report on effects of nicotinamide riboside (NR) on skeletal muscle mitochondrial function, content and morphology. NR supplementation decreases nicotinamide phosphoribosyltransferase (NAMPT) protein abundance in skeletal muscle. NR supplementation does not affect NAD metabolite concentrations in skeletal muscle. Respiration, distribution and quantity of muscle mitochondria are unaffected by NR. NAMPT in skeletal muscle correlates positively with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
114
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 76 publications
(200 reference statements)
8
114
1
Order By: Relevance
“…The low micromolar IC50 of GSK978A achieves muscle NAD elevation similar to that of natural products, such as NR (35), at less than 1% of the effective dose. The relative inability of NR to affect the MDX muscle metabolome likely stems from its poor bioavailability and short (<3 minute) half-life in the blood (8,30), which is consistent with the absence of pharmacodynamics observed in several clinical trials (36)(37)(38). However, both NADmodulating strategies employed in our study failed to improve muscle function.…”
Section: Discussionsupporting
confidence: 83%
“…The low micromolar IC50 of GSK978A achieves muscle NAD elevation similar to that of natural products, such as NR (35), at less than 1% of the effective dose. The relative inability of NR to affect the MDX muscle metabolome likely stems from its poor bioavailability and short (<3 minute) half-life in the blood (8,30), which is consistent with the absence of pharmacodynamics observed in several clinical trials (36)(37)(38). However, both NADmodulating strategies employed in our study failed to improve muscle function.…”
Section: Discussionsupporting
confidence: 83%
“…However, challenges remain in translation of laboratory findings into the design of clinical trials (Gilmour et al 2020). While some early success was found in disease outcomes of amyotrophic lateral sclerosis (ALS) (NCT03489200) (de la Rubia et al 2019), others found no benefit in patients with Alzheimer's disease (NCT00580931) (Phelan et al 2017), or studies of metabolic disorders or mitochondrial bioenergetics in men (NCT02303483) (Dollerup et al 2018(Dollerup et al , 2019a(Dollerup et al , 2019b. Although only a limited number of trials testing NAM, NMN and NR have been recently completed ([ 10) or are currently ongoing (-3), many are actively recruiting (-21) (https://clinicaltrials.gov/) (Lautrup et al 2019) and it will be interesting to see what lessons can be learned about precursor dosage, NAD ?…”
Section: Nad Depletion Oxidative Stress and Autophagy In Physiologimentioning
confidence: 99%
“…Published clinical data indicate that NR is safe and well-tolerated [92][93][94][95]. However, since in men with obesity no improvement has been observed following NR supplementation on some impaired physiological functions associated with obesity (glucose tolerance, mitochondrial functionality) [95][96][97], larger-scale clinical trials are required that may include women and individuals with other diseases.…”
Section: Discussionmentioning
confidence: 99%